ETR 300 Chicken Rearing Production / Mohamad Rosman Sulaiman... [et al.] - Sulaiman, Mohamad Rosman; Mohamad Albar, Mohamad Yusuf; Mahdian, Suraiya; Ishak, Yang Nalis; Rajali, Faizura (2009)
In every progressive firm of organization, top management is really important in order to achieve a standard procedures and quality in every department. This is to ensure the company can achieve their main objectives. For "HOT CHICKEN", our policy has been set which is quality working environment as a guideline for daily operation of the company other than maximizing profits in a just, reasonable manner. Other than that, we are looking forward to improve our share in the market size. We also always try to produce the best and the highest quality products to make our customers really satisfied with us. Another important matter that need to be taken consideration by us is the marketing department full utilization with the market world. Besides that, other related objective of the marketing department is to develop appropriate marketing strategies to ensure the transactions of the business are well-done. Other than that, administration also play the main role in our business. It is to arrange the information activities of each of the company's department so that the company can prevent any unnecessary loss and produce maximum profit. Therefore, administrative office executive provides a support service for all other functions. Financial department, which is the accountant of the company need to prepare the budget needed for the company. It is also to determine the amount of shares that the partnership needs to contribute individually and responsible to any transaction that involves in business. After the budget has been done, every department can start the job immediately. The role for financial also is to prepare an account record for the organization purpose. After all the jobs has been implemented, we hope that we can gain the profit more or less like we planned earlier. We also hope that we will able to supply chickens to more than one chicken processing company in the near future.